Research notes and communications: The effect of product recall announcements on shareholder wealth - Davidson, Wallace N.; Worrell, Dan L. (Strategic Management Journal, 1992)
Abstract Previous research Has found that product recall announcements in the automobile industry are associated with negative abnormal returns. We extend this research by examining announcements of product recalls and products taken off the market outside the automobile industry. We find negative abnormal returns for these announcements and that the returns are significantly more negative when products are replaced (or the purchase price is returned) than when the products are checked and repaired. We find only limited evidence that government‐ordered recalls produce more negative returns than voluntary recalls.